2013
DOI: 10.1111/ejn.12123
|View full text |Cite
|
Sign up to set email alerts
|

Yohimbine anxiogenesis in the elevated plus maze requires hindbrain noradrenergic neurons that target the anterior ventrolateral bed nucleus of the stria terminalis

Abstract: The α2 adrenergic receptor antagonist yohimbine (YO) increases transmitter release from noradrenergic (NA) terminals in cortical and subcortical brain regions, including the bed nucleus of the stria terminalis (BST). YO activates the HPA stress axis and is potently anxiogenic in rats and humans. We previously reported that hindbrain NA neurons within the caudal nucleus of the solitary tract (NST-A2/C2) and ventrolateral medulla (VLM-A1/C1) that innervate the anterior ventrolateral (vl)BST contribute to the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…The current finding is also consistent with evidence that stress-induced reinstatement relies on CRH activity in the bed nucleus of the stria terminalis, (Erb et al, 1998; Ghitza et al, 2006; Shaham et al, 1997). A previous study also found that depletion of NE in the ventrolateral bed nucleus of the stria terminalis blocked the anxiogenic effects of yohimbine (Zheng and Rinaman, 2012). In contrast, results of footshock-induced reinstatement suggest that CRH is particularly important for reinstatement, as CRH infusion induced reinstatement (Erb and Stewart, 1999), while infusion of a CRH antagonist in the bed nucleus of the stria terminalis blocked footshock-induced reinstatement (Erb and Stewart, 1999).…”
Section: Discussionmentioning
confidence: 77%
“…The current finding is also consistent with evidence that stress-induced reinstatement relies on CRH activity in the bed nucleus of the stria terminalis, (Erb et al, 1998; Ghitza et al, 2006; Shaham et al, 1997). A previous study also found that depletion of NE in the ventrolateral bed nucleus of the stria terminalis blocked the anxiogenic effects of yohimbine (Zheng and Rinaman, 2012). In contrast, results of footshock-induced reinstatement suggest that CRH is particularly important for reinstatement, as CRH infusion induced reinstatement (Erb and Stewart, 1999), while infusion of a CRH antagonist in the bed nucleus of the stria terminalis blocked footshock-induced reinstatement (Erb and Stewart, 1999).…”
Section: Discussionmentioning
confidence: 77%
“…Hindbrain GLP-1 neurons and PrRP+ A2 neurons are robustly activated in rats after exposure to visceral or cognitive stressors, and published evidence supports the view that both neural populations contribute to the central control of stress responsiveness and motivated behavior via widespread axonal projections that reach multiple CNS regions implicated in these processes (Banihashemi & Rinaman, 2006;Bechtold & Luckman, 2006;Ellacott et al, 2002;Gu et al, 2013;Holt & Trapp, 2016;Kreisler, Davis, & Rinaman, 2014;Larsen et al, 1997;Lawrence et al, 2000;Lawrence, Liu, Stock, & Luckman, 2004;Llewellyn-Smith et al, 2013;Maniscalco et al, 2013Maniscalco et al, , 2015Maniscalco & Rinaman, 2018;Myers & Rinaman, 2002;Rinaman, 1999bRinaman, , 2003Rinaman, , 2010Zheng & Rinaman, 2013). both neural populations as "stress-sensitive" (Maniscalco et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, when we tried to block the analgesic effect of CR4056 with substances that do not interact with imidazoline I2 receptors, we failed to show a significant antagonism. A relevant exception was the moderate (about 30%) but significant effect of yohimbine, a classical α2-adrenoceptor antagonist, administered at the maximum possible dose not inducing obvious behavioural changes (Arrant et al, 2013;Zheng and Rinaman, 2013). As yohimbine did not antago- Figure 1 (A) Anti-hyperalgesic effect of CR4056 on postoperative paininduced mechanical hyperalgesia in male rats (Randall-Selitto test).…”
Section: Discussionmentioning
confidence: 99%